2019
DOI: 10.1002/sce.21515
|View full text |Cite
|
Sign up to set email alerts
|

Engineering for sustainable communities: Epistemic tools in support of equitable and consequential middle school engineering

Abstract: This study is focused on engineering for sustainable communities (EfSC) in three middle school classrooms.Three in-depth case studies are presented that explore how two related EfSC epistemic toolsets-(a) community engineering and ethnography tools for defining problems, and (b) integrating perspectives in design specification and optimization through iterative design sketch-up and prototyping-work to support the following: (a) Students' recruitment of multiple epistemologies; (b) Navigation of multiple episte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Linkages to students' lived experiences have been shown to foster a more equitable education. For example, Tan et al (2019) demonstrated ways that middle school students can define engineering problems related to their community and use iterative design to balance trade‐offs between technical and social considerations. Their findings echo those of Licona—through such work the students recognized the potential relevance of science and engineering to their community, cultures, and lives.…”
Section: Asset‐based Approaches For Engineering Education With Elsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linkages to students' lived experiences have been shown to foster a more equitable education. For example, Tan et al (2019) demonstrated ways that middle school students can define engineering problems related to their community and use iterative design to balance trade‐offs between technical and social considerations. Their findings echo those of Licona—through such work the students recognized the potential relevance of science and engineering to their community, cultures, and lives.…”
Section: Asset‐based Approaches For Engineering Education With Elsmentioning
confidence: 99%
“…In engineering, these activities can be designed around open-ended tasks, offering multiple solutions that invite engagement in productive disciplinary discourse (Cunningham, 2018;Engle & Conant, 2002). Such engineering solutions are often strengthened through diverse and creative approaches based on the students' lived experiences (Tan et al, 2019). Studies in mathematics and science education point to promising directions for engagement by ELs in engineering experiences with similar attributes.…”
Section: Engaging In Open-ended Tasksmentioning
confidence: 99%
“…The epistemic tool concept has been used in engineering education [5,6] and science education [7], but not in mathematics education. However, the epistemic tool concept is increasingly studied [8] and has already been used across different STEM subjects [1].…”
Section: Stem Learning With Epistemic Toolsmentioning
confidence: 99%
“…Although the research shows that there are various educational resources for science, technology, engineering, and mathematics (STEM) with potential to help teachers create more stimulating and challenging learning environments (e.g., epistemic learning), often teachers fail to obtain educational advantages from their use. orchestrated to improve the quality of students learning, in particular improving epistemic learning [1][2][3][4][5][6][7][8][9][10][11][12][13]. These results make it more urgent for teachers to adopt digital resources as epistemic tools.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a community ethnography approach to hands-on STEM would allow students to learn more about their community members' wants and needs, leading to an understanding of why and how their own knowledge matters. In the context of a teaching method, a community ethnographic perspective on engineering would mean students could research, design and implement solutions to transform their own community (Tan, Calabrese Barton & Benavides, 2019). Engineering becomes a valued community skill, and the process of project-based learning encourages more equity-led teaching, where students learn from and with members of their own community to make it a better place together (Calabrese .…”
Section: Engineering and Ethnographymentioning
confidence: 99%